The using of health belief model on AIDS preventive behaviors among health volunteers - Khair Mohammad Jadgal; Hadi Alizadeh Siuki; Nazanin Shamaian Razavi (Gonabad University of Medical Sciences, 2015)
The prevalence of AIDS/HIV is dramatically increasing worldwide. Iran and other Middle East countries are no exception in this regard. The main aim of this study was to assess the effects AIDS education on Health Belief Model (HBM) constructs among the health volunteers in Roshtkar.The study was conducted as a quasi-experimental trial. One hundred fifty health volunteers were randomly selected and divided into two groups, namely the experimental and control. Having verified the validity and reliability of the questionnaire, it was utilized as a means of data collection. Thirty days after the intervention, the questionnaires were completed again. The data was coded. The collected data were inserted in SPSS software and analyzed by the statistical independent t-test, paired t-test, Pearson Correlation test. The results showed that before intervention, mean scores of knowledge, perceived benefits, barriers, susceptibility and severity, and self-efficacy were not significantly different between the two groups. After training, scores of all variables in intervention group significantly increased. Self-efficacy, perceived benefits, was the strongest predictor within the HBM. AIDS education program could have a better effect on Health Belief Model constructs on AIDS in health volunteers and Household by covered than the AIDS education program by itself.